Who Controls the Voice? The Journalistic Use and the Informational Domain in Vocal Transactors - Fagundes Pase, André; Noll, Gisele; Gomes da Fontoura, Mariana; Dallegrave, Letícia (Brazilian journalism research, 2020)
This article aims to understand the transformations caused by new informational ecosystems in contemporary journalism. This analysis is performed based on news accessed through personal digital assistants embedded in smart speakers. As a methodological procedure, it adopts a multiple case study, defining the vocal transactors of Google (Nest Home/Google Assistant) and Amazon (Echo/Alexa) as its object. Therefore, this paper notes that the inclusion of algorithmic routines and the extension of news content to intelligent voice interfaces requires adaptation for the personalization of information, an ecosystem that is feedback by traditional vehicles, journalists, and people who interact with the artifacts. O presente artigo tem como objetivo compreender as transformações causadas por novos ecossistemas informacionais no jornalismo contemporâneo. Essa análise é realizada a partir de notícias acessadas através de assistentes pessoais digitais embarcados em alto-falantes inteligentes. Como procedimento metodológico, adota o estudo de caso múltiplo, definindo como objeto os transatores vocais da Google (Nest Home/Google Assistant) e da Amazon (Echo/Alexa). Observa, portanto, que a inclusão de rotinas algorítmicas e a extensão de conteúdo noticioso para interfaces de voz inteligentes demanda adaptação para a personalização das informações, ecossistema que é retroalimentado por veículos tradicionais, jornalistas e pessoas que interagem com os artefatos. Este artículo tiene como objetivo comprender las transformaciones causadas por los nuevos ecosistemas informativos en el periodismo contemporáneo. Este análisis se realiza en función de las noticias a las que se accede a través de asistentes digitales personales integrados en altavoces inteligentes. Como procedimiento metodológico, adopta un estudio de caso múltiple, definiendo los transactores vocales de Google (Nest Home/Google Assistant) y Amazon (Echo/Alexa) como su objeto. Señala, por lo tanto, que la inclusión de rutinas algorítmicas y la extensión del contenido de noticias a interfaces de voz inteligentes requiere adaptación para la personalización de la información, un ecosistema que es retroalimentado por vehículos tradicionales, periodistas y personas que interactúan con los artefactos.